1979
DOI: 10.1159/000137289
|View full text |Cite
|
Sign up to set email alerts
|

Human Serum Albumin as a ‘Silent Receptor’ for Drugs and Endogenous Substances

Abstract: Most drugs are bound to human serum albumin (HSA) via a few high affinity binding sites and several sites of much lower affinity. There is now increasing evidence that the actual number of high affinity drug-binding sites of HSA is rather small. Thus, each of these binding sites binds several drugs of very different chemical and pharmacological properties with relative high affinity. On the other hand these drug-binding sites can in some cases be very specific and even stereoselective, as demonstrated by the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
69
0

Year Published

1980
1980
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(72 citation statements)
references
References 24 publications
2
69
0
Order By: Relevance
“…Thus, the binding affinity of albumin is known to depend on its conformation (30), suggesting that a nonspecific interaction might catalyze dissociation by altering the conformation ofthe albumin molecule. Moreover, albumin is known to bind to many different cell types (8) and some hydrophobic surfaces (31).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the binding affinity of albumin is known to depend on its conformation (30), suggesting that a nonspecific interaction might catalyze dissociation by altering the conformation ofthe albumin molecule. Moreover, albumin is known to bind to many different cell types (8) and some hydrophobic surfaces (31).…”
Section: Discussionmentioning
confidence: 99%
“…It has been established that the binding of the anticoagulant drug warfarin to albumin * is affected by this N-B transition [2]. Miiller and WoUert [8], Fehske et al [9], Brodersen et al [10] and Sudlow et al [11] have demonstrated at least two very specific and selective binding sites to be present on the albumin molecule for a large number of highly bound drugs. These sites are the so-called warfarin and diazepam binding site, also denoted as site I and site II by Sudlow et al [11].…”
Section: Introductionmentioning
confidence: 99%
“…17) Protein-ligand interactions play important roles in pharmacology and pharmacodynamics. It is widely accepted that the distribution, free concentration, and metabolism of various compounds can be affected as a result of binding to serum albumins in the blood stream.…”
mentioning
confidence: 99%